Matrix Extension Study: Validation of the Compact Dry TC Method for Enumeration of Total Aerobic Bacteria in Selected Foods. (27th November 2019) - Mizuochi, Shingo; Nelson, Maria; Baylis, Chris; Jewell, Keith; Green, Becky; Limbum, Rob; Fernandez, Maria Cristina; Salfinger, Yvonne; Chen, Yi
Abstract: A validation study was conducted to extend the matrix claim for the Nissui Compact Dry Total Count (TC), Performance Tested Method(s) SM (PTM) Certification No. 010404, to cooked chicken, lettuce, frozen fish, milk powder, and pasteurized whole milk. The method was originally certified by the AOAC Research Institute Performance Tested Method(s) SM Program for raw meat products. The Compact Dry TC is a ready-to-use dry media sheet that is rehydrated by adding 1 mL of diluted sample. A total aerobic colony count can be determined in the sample following 48 h of incubation. Matrix extension studies were conducted by Campden BRI (formerly Campden and Chorleywood Food Research Association Technology Limited), Chipping Campden, UK. Single-laboratory data were collected for cooked chicken, lettuce, frozen fish, and milk powder, whereas a multilaboratory study was conducted on pasteurized milk. Fourteen laboratories participated in the collaborative study. The Compact Dry TC was tested at two time points, 48 ± 3 h and 72 ± 3 h and compared with the current International Organization for Standardization (ISO) method at the time of the study, ISO 4833:2003 (this standard is withdrawn and has been replaced by: ISO 4833-1:2013 and ISO 4833-2:2013), Microbiology of food and animal feeding stuffs–Horizontal method for the enumeration of microorganisms–Colony-count technique at 30°C . The data were logarithmically transformed and evaluated for repeatability (plus reproducibility for pasteurized milk), RSD of repeatability (plus RSD of reproducibility for milk), r 2, and mean difference between methods with 95% confidence interval (CI). A CI outside of (−0.5 to 0.5) on the log10 mean difference was used as the criterion to establish significant statistical difference between methods. No significant differences were found between the Compact Dry TC 48 and 72 h time points, with the exception of one contamination level of cooked chicken and one contamination level of dry milk powder. Mean differences were small at these levels (<0.5 log10 ), but the upper CIs were above 0.5. Statistical differences were indicated between the Compact Dry TC and ISO 4833 in two of five contamination levels tested each for lettuce and frozen fish. In each case, mean differences were >0.5 log10, and the total aerobic colony count was higher for the ISO method. In most cases, mean differences between the Compact Dry and ISO methods were small (<0.5 log10 ) with CIs within the acceptance criterion. Repeatability, reproducibility, and RSD were similar for both methods, and r 2 values were >0.97 for all matrixes. The Compact Dry TC, at 48 h, offers the advantage of a shorter time to results than ISO 4833 in an easy-to-use format.